The space of women's lack of freedom in the cinema of Azerbaijan in 1920s–early 1930s. - Natalia Kazurova (Кавказология, 2023)
The article explores the impact of Soviet propaganda on Azerbaijani cinema in the 1920s and early 1930s, specifically during the transition from avant-garde to social realism. It analyzes three films as case studies: 'In the Name of God' (1925) by A.-M. Sharifzadeh, 'Sevil' (1929) by A. Bek-Nazarian, and 'Ismet' (1934) by M. Mikayilov. The authors discuss the fight against religion as a social institution and the promotion of Soviet ideals to replace customary law (adat). They identify the boundaries of bodily and mental freedom and highlight the lack of freedom experienced by Soviet citizens. The films particularly emphasize women's rights by addressing a breadth of topics, including the role and position of women in family and society, as well as specific plans of action to integrate them into Soviet society. The danger lies in the familiar and everyday aspects of female oppression, originating primarily from the traditional home as the source of authority. A woman's new life begins with a change in her environment and departure from the patriarchal system of interactions. Azerbaijani films reflect both the socio-cultural context and political objectives, aligning with general Soviet policies while also maintaining a distinct national identity that enhances their impact on the local audience.